2022
DOI: 10.1371/journal.pone.0270234
|View full text |Cite
|
Sign up to set email alerts
|

Granular analysis of pathways to care and durations of untreated psychosis: A marginal delay model

Abstract: Objective An extensive international literature demonstrates that understanding pathways to care (PTC) is essential for efforts to reduce community Duration of Untreated Psychosis (DUP). However, knowledge from these studies is difficult to translate to new settings. We present a novel approach to characterize and analyze PTC and demonstrate its value for the design and implementation of early detection efforts. Methods Type and date of every encounter, or node, along the PTC were encoded for 156 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This may have led to quicker help-seeking. Our prior analysis demonstrated that the single largest contributor to DUP in our region was between psychosis onset and first-initiation of help seeking, and that family members were key facilitators 8 . Additionally, reduced patient flow to normally crowded emergency services may have allowed greater attention by clinicians to the identification and management of psychotic symptoms.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This may have led to quicker help-seeking. Our prior analysis demonstrated that the single largest contributor to DUP in our region was between psychosis onset and first-initiation of help seeking, and that family members were key facilitators 8 . Additionally, reduced patient flow to normally crowded emergency services may have allowed greater attention by clinicians to the identification and management of psychotic symptoms.…”
Section: Discussionmentioning
confidence: 84%
“…Both could have led to reductions in DUP-Demand. Since most patients in the catchment receive their first antipsychotic via emergency and inpatient services 8 , this reduction in DUP-Demand is unlikely to be explained by the increasing availability of telehealth services.…”
Section: Discussionmentioning
confidence: 99%